Sari Buah Naga Super merah (Hylocereus costaricensis) Sebagai Pewarna Alami Plak Gigi - Betrik Sefyana Mangiri; Sinar Yani; Silvia Anitasari (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2018)
Dental plaque is a colorless thin layer, is not easily visible on the tooth surface and it causes caries. Disclosing solution is the material that can help us to see dental plaque. Chemical disclosing solution, which now exists, has several disadvantages so we need to develop natural disclosing solution. One of the ingredients in natural disclosing solution that has been studied for its effect is betacyanin, which is contained in super-red dragon fruit (Hylocereus costaricensis). This study aim to observe the coloring effect of super-red dragon fruit juice. The experimental was conducted by measuring plaque index of 20 people, who were not to clean their teeth for 24 hours (two periods), and were eaten the same foods in each period. Examination of plaque index at the end of the first period used chemical disclosing solution contains of erythrosine (FDC Red #3) and the second period used super-red dragon fruit juice. The datas were analyzed by Paired T-test. The results of the plaque index score at the first (2.47815 ± 0.811497), the second (2.7731 ± 1.0512) and did not find a significant difference (p > 0.05). The ability of super-red dragon fruit to coloring dental plaque has no difference with chemical disclosing solution, so it can be used as a natural disclosing solution.